Improving Deaf Children's Writing Skills using Learning Card Series - Mustika, Argiasri; Novianti, Ranti; Nadiyah, Salma (Department of Special Education, 2023)
A person who experiences hearing loss that hinders the process of language information through hearing, whether wearing a hearing aid or not wearing a hearing aid. Whereas someone who lacks hearing is someone who usually uses a hearing aid, the rest of their hearing is enough to allow for the success of the language process through hearing. Language development is a complex process and is something interesting to study. The same goes for the language development of deaf children. So with the problems that occur in deaf children that will also have an impact on how deaf children learn, there is a need for media that can improve the language skills of deaf children, especially in expressive writing ability, where this expressive writing ability is the highest ability in language acquisition (Tarigan: 1994) Skills raised on This research is how to make a whole sentence, practice in using a word that has a blow, get to know many new objects, and how to use time sentences and place description.